Application Of Propositional Calculus In Determining Vb.Net-Based Student Score - Azhari, Mulkan (Al'adzkiya International of Computer Science and Information Technology (AIoCSIT) Journal, 2021)
In this era of globalization, human life is always followed by various problems that must be taken with a decision. There is no day without a decision being made. There is an opinion that all his behavior is a reflection of the results of the decision-making process through his mind so that humans often make decisions. Through the process of identifying the problem until the selection is the best solution and this is what is called the decision-making process. The method used in this journal is propositional calculus. This method has the concept of determining a statement in which there are premises from which then through a truth table, one's statement can be drawn a conclusion. and after understanding what propositional Calculus is we can apply that material by creating a VB.NET-based app project with the aim of facilitating the work of lecturers or other instructors.